Quantitative Estimation of Sorafenib Tosylate Its Pure Form and in Its Tablet Formulation by RP-HPLC Method - R. Kalaichelvi; E. Jayachandran (Journal of Chemistry)
A simple, accurate, specific reverse-phase, high-performance liquid chromatography method has been developed for the determination of sorafenib tosylate in its pure form and its tablets. In this method, sorafenib tosylate was eluted by isocratic mode using a Phenomenex Luna C18 column by a mobile phase composition of acetonitrile and water in the ratio of 82.5 : 17.5, v/v. The flow rate was 1.5 mL/min. The eluted drug was monitored at 265 nm and the method was found to be linear from 5 to 80 μg/mL. The method was validated by linearity, precision, accuracy, LOD, and LOQ. The accuracy report denotes that there is not any interference of additives used in the formulation.